1955
DOI: 10.1111/j.1476-5381.1955.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anti‐cholinesterase Agents on the Rat's Blood Pressure

Abstract: In most species, the effect of systemic intoxication with an anti-cholinesterase-for example, HETP (hexaethyltetraphosphate), TEPP (tetraethyl pyrophosphate), dyflos (diisopropylphosphorofluoridate), Tabun (ethyl NN-dimethylphosphoramidocyanidate), or neostigmine-is predominantly the production of a profound fall in blood pressure (Modell, Krop, Hitchcock and Riker, 1946;Heymans and Jacob, 1947;Lundholm, 1949;Burgen, Keele and Slome, 1949;Verbeke and Votava, 1949;Salerno and Coon, 1949;Holmstedt, 1951). We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1959
1959
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 4 publications
2
33
0
Order By: Relevance
“…Recently Gokhale, Gulati & Joshi (1963) have studied the rise of blood pressure caused by physostigmine when injected into the rat. This rise was described by Dirnhuber & Cullumbine (1955) and independently by Varagi6 in 1955. Gokhale et al (1963) have found that the rise is blocked completely by bretylium, but only partly by hexamethonium.…”
Section: Discussionmentioning
confidence: 96%
“…Recently Gokhale, Gulati & Joshi (1963) have studied the rise of blood pressure caused by physostigmine when injected into the rat. This rise was described by Dirnhuber & Cullumbine (1955) and independently by Varagi6 in 1955. Gokhale et al (1963) have found that the rise is blocked completely by bretylium, but only partly by hexamethonium.…”
Section: Discussionmentioning
confidence: 96%
“…(4) 8mgkg-' i.p. (Lawson, 1943;1944) In the normotensive, non-bled animal, the hypertensive response to cholinomimetics also occurs through the activation of peripheral sympathetic mechanisms and is blocked by guanethidine (Dirnhuber & Cullumbine, 1955;Varagic, 1955;Medacovic & VaragicL, 1957;Brezenoff & Giuliano, 1982). However, in the normotensive animal, the hypertensive response to cholinomimetics involves central muscarinic mechanisms and is in fact abolished by atropine sulphate and scopolamine but not by atropine methylbromide or methylscopolamine (which do not pass the blood-brain barrier).…”
Section: Resultsmentioning
confidence: 99%
“…The pressor response to physostigmine in the rat probably arises from an activation of central nervous sympathetic mechanisms (Varagic, 1955;Dirnhuber & Cullumbine, 1955;Medakovid & Varagid, 1957;Legid & Varagi6, 1961;Varagid & Vojvodic, 1962). Reduction or abolition of the response by antiadrenaline agents, by large doses of hexamethonium and by bretylium or guanethidine suggests that the central stimulant effect of physostigmine may be mediated by way of the established peripheral sympathetic pathways.…”
mentioning
confidence: 99%